P68 International Survey Of Medical students Exposure to Relevant global Surgery (ISOMERS): A cross-sectional study. (8th April 2021) - ,; Bandyopadhyay, Soham; Kanmounye, Ulrick S; Shah, Priyansh; Madani, Katayoun; Beltrano, Joana; Isa, Mashkur A; ,; Bandyopadhyay, Soham; Kanmounye, Ulrick S; Shah, Priyansh; Madani, Katayoun; et al.
Abstract: Introduction: Medical students around the world have been showing an increasing interest in Global Surgery as evident by their participation in various organizations on local and international levels. We set out to evaluate exposure of medical students to global surgery, modes of exposure, whether the exposure meets the needs of students, awareness of the key messages of the Lancet Commission on Global Surgery, global surgery career aspirations and barriers to said aspirations. Methods: We developed the International Survey Of Medical students Exposure to Relevant global Surgery (ISOMERS) study, an online, international, questionnaire-based study. This survey will collect data from final year medical students across the world. The questionnaire utilises a combination of the Likert scale, multiple choice options and free text questions and will be disseminated by email and social media through the International Student Surgical Network, a global surgery student interest group with more than 5, 000 members. Results: Primary outcomes will include exposure to global surgery research, advocacy and education among medical students. We will generate simple descriptive statistics and identify determinants of exposure among medical students and subgroups (country income class and geographic region). Also, we will use multinomial regression analysis to identify confounders and significant dependent variables. Conclusion: The ISOMERS study will identify the level of exposure to global surgery among students during medical education. An understanding of this exposure will be crucial in developing the foundation for global surgery education at the level of undergraduate medical curriculum and furthered in addressing perceived barriers to joining the global surgery workforce.